Bahan Ajar Digital Alternatif Teks Puisi Berdasarkan Proses Kreatif untuk SMP - Suherli Kusmana; Yusida Gloriani; Bella Nurzaman (Ikaprobsi, 2023)
The aim of this research is to overcome the problem of learning loss and the limitations of easily accessible teaching materials outside the classroom. The research method used is research and development. Based on a study of the teaching material needs of Indonesian language teachers at the junior high school level in Cirebon Regency, it is known that 97% of teachers need teaching materials that can develop students' creative abilities, because 93% of them experience difficulties in guiding students to produce poetry containing ideas, feelings, and opinions by paying attention to the building blocks of poetry. From the results of expert validation of the developed teaching materials, it can be seen that the digital teaching materials 'Poetic Texts Based on the Creative Process' are suitable for use. This teaching material can be used as an alternative in learning outside the classroom. Based on extensive trials in 125 schools in Cirebon City, Cirebon Regency, Majalengka, Kuningan and Indramayu, it is known that the digital poetry text teaching material model for junior high schools which was developed based on a creative process is effective in helping teachers achieve learning outcomes. Tujuan penelitian ini adalah untuk mengatasi permasalahan learning loss dan keterbatasan bahan ajar yang mudah diakses di luar kelas. Metode penelitian yang digunakan adalah penelitian dan pengembangan. Berdasarkan studi kebutuhan bahan ajar terhadap guru-guru Bahasa Indonesia pada jenjang SMP di Kabupaten Cirebon diketahui bahwa 97% guru membutuhkan bahan ajar yang dapat mengembangkan kemampuan kreativitas siswa, karena 93% dari mereka mengalami kesulitan dalam menuntun siswa menghasilkan puisi berisi gagasan, perasaan, dan pendapat dengan memperhatikan unsur pembangun puisi. Dari hasil validasi ahli terhadap bahan ajar yang dikembangkan dapat diketahui bahwa bahan ajar digital ‘Teks Puisi Berdasarkan Proses Kreatif’ memiliki kelayakan untuk digunakan. Bahan ajar ini dapat digunakan sebagai alternatif dalam pembelajaran di luar kelas. Berdasarkan uji coba secara luas pada 125 sekolah di Kota Cirebon, Kabupaten Cirebon, Majalengka, Kuningan dan Indramayu diketahui bahwa model bahan ajar digital teks puisi untuk SMP yang dikembangkan berdasarkan proses kreatif memiliki efektivitas dalam membantu guru meraih capaian pembelajaran.